Efek Mediasi Profitabilitas pada Pengaruh Penerapan Green Accounting dan Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan - Nabila Sani Fitri Firdhani; Zulfikar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Green Accounting, Corporate Social Responsibility on Firm Value with Profitability as a mediating variable. This study is a quantitative study using a sample of basic material companies listed on the main board of the Indonesia Stock Exchange (IDX) for the period 2019-2023. Sampling in this study used the purposive sampling method and obtained 30 research samples. This study uses the PROPER rating obtained by the company, the GRI Index, Return on Equity (ROE), and Tobins’q to measure the variables in the study. The research method used is a quantitative approach method by conducting hypothesis testing. The findings in this study indicate that the implementation of Green Accounting has no significant effect on Profitability or Firm Value. Meanwhile, the disclosure of Corporate Social Responsibility has a positive effect on Profitability and Firm Value. Profitability also has a positive effect on Firm Value. In addition, Profitability does not mediate the relationship between Green Accounting and Firm Value, but successfully mediates the relationship between Corporate Social Responsibility and Firm Value.